Dream comes true, UMP Advanced graduand receives PSH Award - Sakinah, Abdullah (2022)
PAYA BESAR, 5 November 2022 - The dream of a TNB Engineering Executive was finally achieved when he successfully obtained a degree of B.Eng (Hons.) Electrical Engineering (Electronics) - Part Time, UMP Advanced.